THE INFLUENCE OF LEARNING FACILITIES ON THE QUALITY OF EDUCATIONAL SERVICES - Wibowo, Ari; Masrur, Muhammad (JLCEdu (Journal of Learning and Character Education), 2023)
This research aims to investigate the influence of learning facilities on the quality of education services in SMA N 1 Kalirejo. Optimal learning facilities are identified as a critical factor in enhancing students' learning experiences and overall education quality. Through a quantitative research approach, data were collected from students, educators, and support staff through surveys and interviews. Regression analysis was employed to measure the relationship between learning facility variables and indicators of education service quality. The research results are expected to provide a profound understanding of the extent to which learning facilities affect the quality of education services, as well as recommendations for improving infrastructure and institutional education policies. This study has the potential to contribute valuable insights for the development of improvement strategies and the management of learning facilities to enhance the quality of education services in the future.